Anatomy and physiology : from science to life - Jenkins, Gail W.; Gerard J. Tortora (Hoboken, New Jersey : Wiley, 2013)
The third edition of Jenkins' Anatomy and Physiology: From Science to Life offers many new and enhanced features. Each chapter of STL is designed and developed into manageable modules of content that place a conceptual order on the facts and terminology. This design is seamlessly mirrored in Wiley PLUS for Anatomy and Physiology.
1 An Introduction to the Human Body -- 2 Chemistry -- 3 Cells -- 4 The Tissue Level of Organization -- 5 The Integumentary System -- 6 Introduction to the Skeletal System -- 7 The Axial Skeleton -- 8 The Appendicular Skeleton -- 9 Articulations -- 10 Muscle Tissue -- 11 The Muscular System -- 12 Introduction to the Nervous System -- 13 The Central Nervous System -- 14 The Peripheral Nervous System -- 15 Sensory, Motor, and Integrative Systems --16 The Special Senses -- 17 The Endocrine System -- 18 The Cardiovascular System: The Blood -- 19 The Cardiovascular System: The Heart -- 20 The Cardiovascular System: Blood Vessels and Hemodynamics -- 21 The Lymphatic and Immune Systems -- 22 The Respiratory System -- 23 The Digestive System -- 24 The Urinary System -- 25 The Reproductive Systems.
Includes index.
Keywords: HUMAN ANATOMY